Determinants of User Satisfaction SATe Website Application (Integrated Accounting System) using the Webqual 4.0 Method - Yudha, Therasyamia Novtriana; Binastuti, Sugiharti (TIN: Terapan Informatika Nusantara, 2025)
The implementation of E-Government in various government sectors, including Bekasi City, encourages the development of effective and efficient information systems. One example is the Integrated Accounting System (SATe). This study aims to analyze the Influence of Usability, Information quality and Interaction quality on User satisfaction on the SATe Website application using the Webqual 4.0 method. Webqual is one of the methods or techniques for measuring Website quality based on end user perceptions. Website quality can be assessed by three dimensions of Webqual 4.0 consisting of user quality, information quality and interaction quality. The objects of the study are Usability, Information quality, Interaction quality and User satisfaction. The subjects in this study were users of the SATe Website application. The data used are primary data collected from respondents using a questionnaire instrument, namely 108 respondents consisting of Treasurers and Assistant Treasurers of SKPD Bekasi City and Accounting employees of BPKAD Bekasi City who use the SATe Website application. Based on the results of the research that has been conducted, it can be concluded that Usability, Information quality, and Interaction quality simultaneously have a significant influence on the level of user satisfaction of the SATe Website application, while partially, the Usability and Interaction quality variables have a significant influence on user satisfaction of the SATe Website application, but Information quality does not affect User satisfaction.